Effect of microstructure on tensile properties, impact toughness and fracture toughness of TC21 alloy. (15th October 2019) - Wen, Xin; Wan, Mingpan; Huang, Chaowen; Tan, Yuanbiao; Lei, Min; Liang, Yilong; Cai, Xin
Abstract: This paper aims to reveal how multi-level lamellar microstructure influences strength and toughness of TC21 alloy after different solution treatment ranging from 980 °C to 1020 °C and annealed at 770 °C. Microstructural characterization was performed by using optical microscopy (OM), scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), transmission electron microscope (TEM), and image analysis software. Results show that the size of β grains ( d β ) grows significantly while α colony ( d c ) increases slowly with the solution temperature increases. Meanwhile, α plate ( d α ) presents an opposite tendency. In addition, the Hall-Petch formula was applied to reveal the relationship between multi-level microstructure (including prior β grain, α colony and α plate) and strength and toughness of the alloy; α colony could be a key microstructure unit correlated to strength of the alloy. Besides, α plate obeys the Hall-Petch relationship with toughness. Meanwhile, it is confirmed by EBSD that more α plate were cut with the increasing size of the multi-level lamellar microstructure. The larger α colony size is, the stronger the interaction between the crack and α plate. Thus, α plate was regarded as the key microstructure unit for influencing toughness because it strongly hinders the crack initiation and growth. Graphical abstract: In order to understand crack propagation path and propagation mechanism of TC21 alloy, the EBSD observation on fracture surface were investigated in detail, then the schematic illustration for the crack propagation was made according to experiment results.Unlabelled Image Highlights: Different mechanical properties depend on different level microstructure unit. α colony could be a key microstructure unit correlated to strength. α plate could be a key microstructure unit correlated to toughness. Different mechanical variation tendency is attributed to different microstructure unit correlated to performance.